Pollen tip growth : from biophysical aspects to systems biology - Obermeyer, Gerhard; Feijó, José (Springer, 2017)
This book focuses on the biophysical aspects of tip growth: How do physical parameters like pressure, water potential, electrical fields, or ion currents contribute to and influence this specialized and highly dynamic form of cell growth? It provides an updated and balanced overview of the current state of knowledge and future research perspectives regarding how pollen tubes' growth is driven and regulated by molecular interactions underlying the cellular processes. The individual chapters address topics ranging from molecular biophysical concepts to comprehensive omic studies and computational modeling of the tip growth process. In addition, a chapter on root hair cells is included to provide an alternative view on the underlying molecular principles of tip growth in general. Each chapter provides a summary of cutting-edge techniques, results and experimental data; a statement, hypothesis or conclusion on the importance of the aspect described for tip growth, particularly pollen tip growth; and addresses open gaps in our understanding and potential approaches to remedying them. The book offers experimental and theoretical solutions to help established researchers and newcomers to the field alike solve the many mysterious behaviors of pollen tube tips.
Keywords: Pollination.; Pollen.; elektronické knihy; electronic books